Numerical Simulations of Staged Biomass Grate Fired Combustion with an Emphasis on NOx Emissions. (August 2015) - Bugge, Mette; Skreiberg, Øyvind; Haugen, Nils Erland L.; Carlsson, Per; Houshfar, Ehsan; Løvås, Terese
Abstract: In the present paper NOx emissions from biomass combustion was studied, with the objective to demonstrate the applicability of stationary computational fluid dynamics simulations, including a detailed representation of the gas phase chemistry, to a multi-fuel lab-scale grate fired reactor using biomass as fuel. In biomass combustion applications, the most significant route for NOx formation is the fuel NOx mechanism. The formation of fuel NOx is very complex and sensitive to fuel composition and combustion conditions. And hence, accurate predictions of fuel NOx formation from biomass combustion rely heavily on the use of chemical kinetics with sufficient level of details. In the present work we use computational fluid dynamics together with three gas phase reaction mechanisms; one detailed mechanism consisting of 81 species and 1401 reactions, and two skeletal mechanisms with 49 and 36 species respectively. Using the detailed mechanism (81 species), the results show a high NOx reduction at a primary excess air ratio of 0.8, comparable to the NOx emission reduction level achieved in the corresponding experiment, demonstrating both the validity of the model and the potential of NOx reduction by staged air combustion.